2022 IEEE 19th Annual Consumer Communications &Amp; Networking Conference (CCNC) 2022
DOI: 10.1109/ccnc49033.2022.9700505
|View full text |Cite
|
Sign up to set email alerts
|

On Frame Fingerprinting and Controller Area Networks Security in Connected Vehicles

Abstract: Modern connected vehicles are equipped with a large number of sensors, which enable a wide range of services that can improve overall traffic safety and efficiency. However, remote access to connected vehicles also introduces new security issues affecting both inter and intra-vehicle communications. In fact, existing intra-vehicle communication systems, such as Controller Area Network (CAN), lack security features, such as encryption and secure authentication for Electronic Control Units (ECUs). Instead, Origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The frame fingerprinting approach presented in [11] revolves around four distinctive aspects of the CAN traffic: the payload length, the dynamic behavior of the payload bits, the sending frequency, and the frame priority. The approach in [11] makes the following assumption regarding the frame priority: the attribution of new sets of frame IDs in newly released vehicle models should preserve their priority. This leaves no space for manipulation against frame fingerprinting.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The frame fingerprinting approach presented in [11] revolves around four distinctive aspects of the CAN traffic: the payload length, the dynamic behavior of the payload bits, the sending frequency, and the frame priority. The approach in [11] makes the following assumption regarding the frame priority: the attribution of new sets of frame IDs in newly released vehicle models should preserve their priority. This leaves no space for manipulation against frame fingerprinting.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it was demonstrated that fully automated reverse engineering can be achieved by finding a correspondence between the frames of a target vehicle and the ground truth of previously reverse engineered vehicles. The match can be found based on the ID of frames (if it has been preserved in the target vehicle [10]), or through ML fingerprinting (if the ID has been changed/anonymized [11]).…”
Section: Background and Related Workmentioning
confidence: 99%
See 3 more Smart Citations